2018
DOI: 10.3390/nu10020234
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bone Mineral Density of Femoral Neck and Geriatric Nutritional Risk Index in Rheumatoid Arthritis Patients Treated with Biological Disease-Modifying Anti-Rheumatic Drugs

Abstract: Treatment of rheumatoid arthritis (RA) with biological disease-modifying anti-rheumatic drugs (bDMARDs) induces rapid remission. However, osteoporosis and its management remains a problem. The Geriatric Nutritional Risk Index (GNRI) evaluates the risk of malnutrition-related complications in elderly patients and has been shown to be a significant predictor of many diseases. We evaluated the correlation between GNRI and RA activity. In addition, risk factors for femoral neck bone loss were evaluated in RA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…As a consequence, it has been proven that GNRI can be applied as a convenient and reliable indicator for the BMD conditions of patients with the above diseases. In addition, it has been shown that there is a dramatically inverse relationship between GNRI and BMD in rheumatoid arthritis patients. As the association is caused by protein that originates from animals and plants , it is crucial to guarantee the intake of enough protein from the diet.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it has been proven that GNRI can be applied as a convenient and reliable indicator for the BMD conditions of patients with the above diseases. In addition, it has been shown that there is a dramatically inverse relationship between GNRI and BMD in rheumatoid arthritis patients. As the association is caused by protein that originates from animals and plants , it is crucial to guarantee the intake of enough protein from the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis is a chronic representative autoimmune disease associated with inflammation and nutritional status . In our study, we assessed the ALB‐dNLR score, which was based on albumin and dNLR in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Rheumatoid arthritis is a chronic representative autoimmune disease associated with inflammation and nutritional status. 19,20 In our study, we assessed the ALB-dNLR score, which was based on albumin and dNLR in RA patients. The results found that RA patients tend to have higher ALB-dNLR scores than OA patients or healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The GNRI, which takes both serum albumin and BMI into account, has also been associated with BMD in several recent studies. In a study of 146 Japanese patients, Tokumoto et al reported that a low GNRI was a risk factor for lower BMD of the femoral neck in patients with rheumatoid arthritis [35]. In addition, Wang et al reported a positive relationship between GNRI and BMD in Chinese patients with type 2 diabetes mellitus in a study of 225 men and 192 women [36].…”
Section: Discussionmentioning
confidence: 99%